Pathophysiological alterations of left ventricular myocardial systolic function during normal pregnancy assessed by speckle tracking echocardiography: a prospective cohort echocardiography study. (4th February 2022) - Tryfou, E; Kostakou, P; Kostopoulos, V; Mahairiotis, C; Mihas, K; Olympios, C; Paraskevaidis, I; Kouris, N
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Pregnancy induces a variety of haemodynamic and morphological changes, leading to the amplification of cardiac pumping function. These changes do not cause any significant left ventricular (LV) dysfunction by using conventional echocardiographic indices, but it is not fully elucidated whether subclinical or/and reversible myocardial dysfunction is provoked during pregnancy. Two-dimensional speckle tracking echocardiography (2D-STE) can detect subclinical myocardial dysfunction even when conventional echocardiography reveal LV normal ejection fraction (LVEF).Purpose: The aim of this study was to evaluate whether LV systolic performance is impaired during normal low risk pregnancy by using both conventional 2D and 3D echo indices and 2D-STE. Materials and methods: One hundred and twelve consecutive pregnant women without any history of heart disease were prospectively recruited. They underwent serial echocardiographic evaluation in each pregnancy trimester (1st: 8th-12th week, 2nd: 22th-26th week, 3rd: 32-36th week) and 6 months after delivery (time indicated as 4). LV dimensions, relative wall thickness (RWT), 2D-LVEF, 3D-LVEF, systolic S wave from Tissue Doppler Imaging, LV global longitudinal strain (LVGLS), LV global circumferential strain (LVGCS) and LV-twist were measured and compared to 31 nulliparous women of similar age, who served as a control group (c).Results: Progressive eccentric LV hypertrophy was observed during pregnancy, which was subsided postpartum (p1-2 = 0.08, p2-3= 0.002, p3-4 = 0.001, p1-3 < 0.001, p1-4= 0.789), while no significant change in LV dimensions was found. 2D-LVEF, 3D-LVEF and S wave values were not significantly different among the three trimesters, postpartum and controls. LVGLS progressively decreased during pregnancy (1st:-21.71 ± 2.13%, 2nd: -21.20 ± 2.30%, 3rd: -19.82 ± 2.10%, 4th: -21.81 ± 2.05%, c: -21.71 ± 2.2[E1]%, overall p < 0, 001 ) and returned to normal during puerperium. No significant difference was noted in LVGCS (1st: -18.08 ± 5.54%, 2nd: -18.57 ± 3.41%, 3rd: -18.20 ± 3.33%, 4th: -17.95 ± 3.39%, c: -18.8 ± 2.2%, p > 0.3). LV-Twist was significantly higher in the 1st trimester compared to controls (p= 0.04) and remained constantly high during the rest of the pregnancy and puerperium (1st:13.80 ± 5.09°, 2nd :13.46 ± 5.35°, 3rd:13.58 ± 4.32°, 4th:13.37 ± 4.26°, c: 11.5 ± 4.3°, ).Conclusion: Left ventricular subclinical dysfunction seems to occur in the longitudinal axis even in low risk individuals with normal pregnancy. Increased torsional movement of the heart seems to counterbalance the temporal impairment of longitudinal systolic function.